Wilhelm von Humboldt and transcultural communication in a multicultural world translating humanity - Walker, John 1956- (Camden House, 2022)
Shows that the work of Wilhelm von Humboldt (1767-1835) forms a philosophy of dialogue and communication that is crucially relevant to contemporary debates in the Humanities
Title from publisher's bibliographic system (viewed on 03 Jan 2023)
Keywords: Humboldt, Wilhelm von / 1767-1835; Humboldt, Wilhelm von -- 1767-1835; Intercultural communication; Language and languages / Philosophy; Sprachphilosophie; Interkulturelle Kompetenz